MEMORABLE MUSIC AND COGNITIVE DEVELOPMENT IN EMERGING ADULTHOOD: A SCIENTIFIC PERSPECTIVE - Hidayat, Luthfi; A, Shintia Anggraeni; Dahlan, Tina Hayati; Pangestu, Fachri Hamzah (JOURNAL OF SCIENCE EDUCATION AND PRACTICE, 2024)
Music has a remarkable ability to influence mood, improve concentration and stimulate human emotions. In the context of a learning simulation involving reading, listening, writing and eating snacks, memorable music was found to have a positive impact on adult learners' cognitive processes. From a study involving three adult learners aged between 18-29 years old, purposive non-random sampling was used to ensure inclusion criteria as adult learners without hearing loss. The research used a qualitative study with data collected through interviews and observations and thematic analysis. This research shows that memorable music has a positive impact on adult learners' cognitive processes. The integration of music in learning improved participants' attention, memory and thinking. Understanding the complex interactions between music and cognitive processes provides valuable insights for psychological and biological understanding, contributing to effective applications in rehabilitation, treatment and education.